PENGARUH KOMPETENSI, PENGEMBANGAN KARIR, PENDIDIKAN DAN PELATIHAN (DIKLAT) TERHADAP KNERJA PEGAWAI DIREKTORAT JENDERAL PERIMBANGAN KEUANGAN - Dono Wirotomo; Popy Novita Pasaribu (Universitas Mercu Buana, 2015)
Abstract. The success of the organization in achieving its goals supported by factors internaland external to the organization, where the internal side of the organization should be get firstattention to achieve maximum performance. This study aims to determine the effect ofcompetency, career development and training on employee performance of the DirectorateGeneral of Fiscal Balance, Ministry of Finance. The method used is descriptive quantitative.The data used are primary data collected by questionnaire and also secondary data. Thepopulation in this study were all employees as many as 387 people. The samples are taken byrandom sampling technique, using the Slovin‟s formula to take 80 people for samples. Thevariables in this study consisted of independent variables that are competency, careerdevelopment and training, while the dependent variable is the performance of employees. Thevariable measured with Likert Scale and hypothesis testing using multiple linear regression byusing t test and F test.Results of this study concluded that: 1) in partially competency hadpositive and significant impact on employee performance; 2) in partially career developmentprovide uneffect on employee performance; 3) in partially training had positive andsignificant impact on employee performance; and 4) in simultaneously competency, careerdevelopment and training have positive and significant impact on employee performance.Competency is the most influence variable on employee performance.Keywords: Competency, Career Development, Training and Employee Performance